(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article is devoted to a comparative criminal-legal analysis of norms on responsibility for crimes against sexual freedom and sexual integrity according to the Criminal Code of Ukraine, France and Germany. The inadequacy of the criminal law protection of public relations against acts of exhibitionism in Ukraine has been proven (Articles 222-32 of the Criminal Code of France and § 183 of the Criminal Code of Germany). There is a need to criminalize public display of genitals or public performance of real or simulated sexual intercourse. A qualifying sign of rape under the Criminal Code of France is recognized as an act, as a result of which the victim was brought into contact with the criminal through the use of an electronic communication network to spread messages among an unspecified number of people. From the point of view of the Criminal Code of Ukraine, the stated circumstance of the interruption of a criminally illegal act can be taken into account when assessing the actions of the perpetrator as preparation for rape. At the same time, as a qualifying circumstance, such actions are not taken into account in Art. 152 of the Criminal Code of Ukraine. Acts of a sexual nature on the part of a person who works in an educational, educational or social support institution for children are assessed as actions with an increased degree of public danger according to the Criminal Code of the Federal Republic of Germany. For the Criminal Code of Ukraine, this approach is not typical, but it is worth borrowing.